Study on the flow around a cylinder by candle flame. Issue 1 (1st June 2022) - Huang, Junwei; Zhang, Pengyu; Xie, Zhuoxuan; Zhao, Haojie; Xu, Chenkun; Chi, Jing; Lu, Huiping
Abstract: Interferometric measurement, schlieren method and shadow graph are commonly used to observe the low-speed steady flow. It is difficult to directly observe the flow direction in the experiment of flow around a cylinder at medium and high Reynolds number. On this premise, this paper mainly studies the relationship between the movement state of candle flame and the direction of candle airflow. This paper studies the influence of different wind speeds on the flow around a circular cylinder at medium and high Reynolds numbers. The innovation of this paper is to propose a new idea to directly observe the complex air flow, and to compare the candle flame state under different experimental conditions and the calculation images of different turbulence models.